Comparative review of pharmacological therapies in individuals with HER2-positive advanced breast cancer with focus on hormone receptor subgroups - Umemneku-Chikere, Chinyereugo M.; Ayodele, Olubukola; Soares, Marta; Khan, Sam; Abrams, Keith; Owen, Rhiannon; Bujkiewicz, Sylwia (Frontiers in Oncology, 2022)
Breast cancer is the fifth leading cause of cancer related deaths worldwide. Randomised controlled trials (RCTs) of targeted therapies in human epidermal receptor 2 (HER2) positive advanced breast cancer (ABC) have provided evidence base for regulatory and reimbursement agencies to appraise the use of cancer therapies in clinical practice. However, a subset of these patients harbour additional biomarkers e.g. a positive hormone receptor status which may be more amenable to therapy, and improve overall survival. This review seeks to explore the reporting of evidence for treatment effects by hormone receptor status using the RCTs evidence of targeted therapies for HER2 positive ABC patients. PRISMA guidelines were followed to identify published RCTs. Extracted data were synthesised using network meta-analysis and relative effects of HER2 positive targeted therapies were obtained. We identified a gap in the reporting of the effectiveness of therapies by hormone receptor subgroups as only 15 out of 42 identified RCTs reported hormone receptor status analyses; majority of which reported progression free survival (PFS), but not overall survival (OS) or overall response rate (ORR). In conclusion, we recommend that future trials in ABC should report the effect of cancer therapies in hormone receptor subgroups.